Knowledge of Mother About Nutrition Fulfillment and Stunting Incidence in Pasirbatang Village, Tasikmalaya - ana samiatul millah; Tika Sastraprawira; Yayi Siti Haeriyah (Insights in Public Health Journal, 2022)
The role of parents, particularly mothers, is very important in the process of child development. Limited knowledge of mothers can affect the nutritional status of infants and increase the risk of stunting. This study aims to determine the relationship between mothers' knowledge of balanced nutritional food and the incidence of stunting in toddlers in Pasirbatang Village, Tasikmalaya Regency in 2022. This is a quantitative research design with a cross-sectional approach with a sample of 70 mothers with toddlers. Sampling in this study was stratified random sampling. The variables studied were mother's knowledge and the incidence of stunting, with the research instrument in the form of a questionnaire. The results showed that there was no significant relationship between mother's knowledge about infant nutrition fulfillment and the incidence of stunting in Pasirbatang, Tasikmalaya Regency, 2022 because the <p-value (0.05 <0.769). This is possible because there are other variables that influence the incidence of stunting such as parenting style, exclusive breastfeeding and infectious diseases. Parents must equip themselves with the knowledge and skills to meet the nutritional needs of their babies so as to avoid the risk of stunting